Blockchain in Health Care Innovation: Literature Review and Case Study From a Business Ecosystem Perspective - Chang, Shuchih Ernest; Chen, YiChian (JMIR Publications, 2020)
BackgroundBlockchain technology is leveraging its innovative potential in various sectors and its transformation of business-related processes has drawn much attention. Topics of research interest have focused on medical and health care applications, while research implications have generally concluded in system design, literature reviews, and case studies. However, a general overview and knowledge about the impact on the health care ecosystem is limited. ObjectiveThis paper explores a potential paradigm shift and ecosystem evolution in health care utilizing blockchain technology. MethodsA literature review with a case study on a pioneering initiative was conducted. With a systematic life cycle analysis, this study sheds light on the evolutionary development of blockchain in health care scenarios and its interactive relationship among stakeholders. ResultsFour stages-birth, expansion, leadership, and self-renewal or death-in the life cycle of the business ecosystem were explored to elucidate the evolving trajectories of blockchain-based health care implementation. Focused impacts on the traditional health care industry are highlighted within each stage to further support the potential health care paradigm shift in the future. ConclusionsThis paper enriches the existing body of literature in this field by illustrating the potential of blockchain in fulfilling stakeholders' needs and elucidating the phenomenon of coevolution within the health care ecosystem. Blockchain not only catalyzes the interactions among players but also facilitates the formation of the ecosystem life cycle. The collaborative network linked by blockchain may play a critical role on value creation, transfer, and sharing among the health care community. Future efforts may focus on empirical or case studies to validate the proposed evolution of the health care ecosystem.